Local wisdom and organizational support in enhancing teachers’ organizational commitment - Linawati, Linawati; Hardhienata, Soewarto; Setyaningsih, Sri (Edelweiss Applied Science and Technology, 2026)
This study develops and tests a conceptual model aimed at enhancing teachers’ organizational commitment by integrating elements of local wisdom, specifically silih asih (mutual compassion) and silih asuh (mutual guidance), with organizational support mechanisms, represented by transformational leadership and career development. The enhancement strategy was formulated using the Modeling and Optimization of Management Resource Strengthening (POP-SDM) approach. Data were collected from foundation-appointed elementary school teachers in Bogor City, Indonesia, using a multistage random sampling technique. The findings indicate that transformational leadership and career development significantly influence organizational commitment both directly and indirectly through the mediating roles of silih asih and silih asuh. The SITOREM analysis identified several strategic indicators that require improvement, including equity, social responsibility, dedication, respect, inspirational motivation, individual support, self-awareness, skills development, alternatives, organizational investment, and cost perspective. This study contributes to the theoretical discourse by integrating culturally rooted values into organizational behavior frameworks. It also provides practical recommendations for educational leaders to strengthen teachers’ organizational commitment through leadership development, career advancement initiatives, and culturally responsive interventions.